Effect of preparation method in the properties of iron oxide catalysts for fenton reaction - Fabiana Maria Barbosa; Andre Rosa Martins (The Journal of Engineering and Exact Sciences)
This work discusses methods of preparing iron oxide for the Fenton reaction, using methylene blue as a model molecule. The solids were prepared by precipitation, complexation, combustion, and decomposition and characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electronic microscopy, energy dispersive X-ray spectroscopy, specific surface area measurement and were evaluated for methylene blue removal. The method influenced the structural and surface properties of the solids, and consequently the catalytic performance of the solids. The solid prepared by precipitation showed the highest area, amorphous phase, and the best performance in the adsorption test. On the other hand, the combustion method favored the formation of hematite and traces of magnetite.  The solid prepared by this method showed higher values of the methylene blue dye oxidation./Este trabalho discute métodos de preparação de óxido de ferro para a reação de Fenton, utilizando o azul de metileno como molécula modelo. Os sólidos foram preparados por precipitação, complexação, combustão e decomposição e caracterizados por espectroscopia de infravermelho por transformada de Fourier, difração de raios-X, microscopia eletrônica de varredura, espectroscopia de energia dispersiva de raios-X, medição de área superficial específica e foram avaliados para remoção de azul de metileno. O método influenciou as propriedades estruturais e superficiais dos sólidos e, consequentemente, o desempenho catalítico dos sólidos. O sólido preparado por precipitação apresentou a maior área, fase amorfa e melhor desempenho no teste de adsorção. Por outro lado, o método de combustão favoreceu a formação de hematita e vestígios de magnetita.  O sólido preparado por este método apresentou valores mais altos de oxidação do azul de metileno.